2007
DOI: 10.1590/s1413-35552007000200002
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia of ageing: functional, structural and biochemical alterations

Abstract: Aging is associated with a progressive decline of muscle mass, strength, and quality, a condition described as sarcopenia of aging. Despite the significance of skeletal muscle atrophy, the mechanisms responsible for the deterioration of muscle performance are only partially understood. The purpose of this review is to highlight cellular, molecular and biochemical changes that contribute to age-related muscle weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
18

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 42 publications
0
18
0
18
Order By: Relevance
“…[1][2][3] These changes to muscle composition result from muscle fiber atrophy, reduction in the production of certain hormones (testosterone, adrenal androgens and growth hormone) and inappropriate food intake, among other factors. [1][2][3][4][5][6] The decrease in muscle strength resulting from sarcopenia causes significant functional loss with regard to performing activities of daily living (ADLs), and this is the main etiological factor in the development of functional dependence among elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] These changes to muscle composition result from muscle fiber atrophy, reduction in the production of certain hormones (testosterone, adrenal androgens and growth hormone) and inappropriate food intake, among other factors. [1][2][3][4][5][6] The decrease in muscle strength resulting from sarcopenia causes significant functional loss with regard to performing activities of daily living (ADLs), and this is the main etiological factor in the development of functional dependence among elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The decrease in muscle strength resulting from sarcopenia causes significant functional loss with regard to performing activities of daily living (ADLs), and this is the main etiological factor in the development of functional dependence among elderly individuals. 1,3,[6][7][8][9][10][11][12] The association between muscle strength and functional independence has been pointed out in the literature, and the study by Janssen et al 8 deserves special attention.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is characterized by morphological and physiological changes, such as loss of muscle strength, flexibility, and balance, and other deficits in physical function 2,3 , particularly in women 4 . In conjunction with these processes, there are variations in body composition and anthropometry (a reduction in weight, height, and bone mineral density) and these are exacerbated by the more sedentary lifestyle of older individuals 5,6 , which affects their quality of life 7 and increases the risk of falls, especially in women 8 . Furthermore, it has been identified that Brazilian women show variations in their fitness relative to other populations 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of muscle mass associated with aging seems to be the primary factor responsible for reduction in muscle strength and power and the consequent loss of functional mobility in elderly people [2][3][4] . It is estimated that aging is associated with 20% to 40% of the decrease in muscle strength and power at 70-80 years of age and with still greater reductions (50%) at 90 years of age in both sexes [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%